Protective effects of Dioscorea alata and D. rotundata extracts on liver, pancreas, and kidney in alloxan-induced diabetic guinea pigs - Raphaël Lombe Mputu; Léopold Kazadi Mfumu Mulumba; Jeff Bekomo Iteku; Odette Ngandu Kabena; Jean-Pau (Orapuh, Inc., 2024)
Introduction Diabetes mellitus is a chronic metabolic disease that affects a large fraction of the world's population. In addition to the many complications associated with it, the lack of effectiveness and insufficiency of current treatments have driven the WHO to return to traditional medicine, which generally involves the use of plant materials as remedies. Purpose This study investigates the protective effects of Dioscorea alata and D. rotundata extracts on the liver, pancreas, and kidney in alloxan-induced diabetic guinea pigs. Methods Diabetes was induced by a single intraperitoneal injection of alloxan (150 mg/kg). Post-induction, guinea pigs (Cavia porcellus L.) were treated orally with Dioscorea alata and D. rotundata extracts (200 mg/kg and 400 mg/kg, respectively) for 21 days. The liver, pancreas, and kidneys were assessed for histopathological changes. Two standard synthetic antidiabetics (insulin 5 IU/100g and glibenclamide 5 mg/kg) were used as positive controls. Results Histopathological examination revealed marked improvement in the tissue morphology of the liver, pancreas, and kidneys in the treated groups compared to the untreated group. The renal parenchyma showed a fairly normal structure, with the Malpighian glomerulus clearly visible, exhibiting hyperplastic cell nuclei in full regeneration. Conclusion Tuber extracts from these two yam species have shown potential to repair and regenerate tissue damaged by the deleterious effects of alloxan-induced free radicals and permanent hyperglycemia during diabetes. The evident antidiabetic and cytoprotective potential of these plant species could be utilized for the development of biologically active natural molecules for the treatment of diabetes mellitus and its complications. The study is limited by its short duration, and further long-term studies with varied dosage regimens are recommended to better understand the effects of these extracts. Additional research should explore the specific bioactive compounds responsible for the observed protective effects and their mechanisms of action.